Dorsal Root Ganglion Stimulation as a Salvage Treatment for Complex Regional Pain Syndrome Refractory to Dorsal Column Spinal Cord Stimulation: A Case Series. Issue 7 (16th June 2017) - Yang, Ajax; Hunter, Corey W.
Abstract : Objective: The efficacy of traditional spinal cord stimulation (t‐SCS) tends to decay over time in patients with complex regional pain syndrome (CRPS). While it has been shown that dorsal root ganglion (DRG) stimulation is extremely effective in t‐SCS‐naïve patients with CRPS, its efficacy in patients who had previously failed t‐SCS is unknown. Given that DRG‐SCS and t‐SCS target different spinal pathways, a failure with t‐SCS should not automatically preclude a patient from attempting DRG‐SCS. Materials and Methods: Two patients with lower extremity CRPS, previously implanted with t‐SCS systems, experienced relapses in the pain despite exhaustive reprogramming. Both patients were offered DRG stimulation as a means to salvage treatment. Results: Patient 1 reported 90% pain reduction with significant gait improvement during the DRG stimulation trial. The patient subsequently proceeded to implant and have the t‐SCS implantable pulse generator explanted. Patient 2 was unable to undergo a trial with DRG‐SCS because of health insurance constraints, so she elected to undergo a surgical revision of her existing system whereby a DRG‐SCS system was added to the existing t‐SCS to create a hybrid system with two implantable pulse generators. The patient reported an immediate improvement in pain because of the introduction of the DRG‐SCS. Additionally, she was instructed to document her pain scores with each system on individually, as well as with both on—her pain scores were at the lowest with the DRG‐SCS on by itself. At eight‐month follow‐up, both patients reported sustained pain improvement and retained their functional gains. Conclusions: Our case series demonstrates that a failure of t‐SCS is not necessarily a failure of neurostimulation as a whole. The efficacy of DRG‐SCS is independent of prior t‐SCS therapy outcomes in these two patients and a history of t‐SCS failure serves no predictive value in these two patients for future DRG stimulation success. Therefore, DRG‐SCS can be considered as a reasonable next‐step to salvage patients with CRPS who had failed other SCS treatments.